2021
DOI: 10.1530/rep-21-0123
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antisperm antibodies on human male reproductive function: an update

Abstract: Immune infertility occurs due to the presence of antisperm antibodies (ASA). This type of infertility has a relatively low prevalence (2.6-6.6% in infertile men), and its etiology, risk factors, targets and consequences for male fertility are not completely understood. While it is largely accepted that abnormalities in the blood-testis barrier and/or blood-epididymal barrier are the main factors behind its etiology, and that sperm motility is the most frequently reported altered parameter, few are the well-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 138 publications
1
14
0
Order By: Relevance
“…According to the age category, the studied cases demonstrated lower records of sperm morphology in the age group 40-49 and ≥50 years. These outcomes were in agreement with several investigation studies of aging effect on fertility (Ahmed, et al, 2019;Silva, Ramalho-Santos and Amaral, 2021). In addition, the progressive sperm motility for the age category ≥50 years was below the reference value of the WHO (Björndahl and Brown, 2022) that was in agreement with similar studies (Stewart and Kim, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the age category, the studied cases demonstrated lower records of sperm morphology in the age group 40-49 and ≥50 years. These outcomes were in agreement with several investigation studies of aging effect on fertility (Ahmed, et al, 2019;Silva, Ramalho-Santos and Amaral, 2021). In addition, the progressive sperm motility for the age category ≥50 years was below the reference value of the WHO (Björndahl and Brown, 2022) that was in agreement with similar studies (Stewart and Kim, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The findings showed no significant difference between the direct and indirect techniques for detecting both classes of IgA according to their distributions on sperm parts in all subjects, including the primary and secondary types of infertility, which have been confirmed by previous studies. ASAs affect virtually all components of sperm, diminished sperm-oocyte binding, faulty zona pellucida penetration cervical mucus penetration, and sperm survival (Silva, Ramalho-Santos and Amaral, 2021). Furthermore, the ASAs linked to abnormal embryo development by retarding the cleavage process, blocking the initiation of the embryo, and most significantly affecting fertilization rates when localized both at the head and the tail tip levels of sperm.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of all data cited above, the link between the presence of ASAs in men and infertility continues to be disputed, and it is unclear whether ASAs adversely affect the outcome of in vitro fertilization (IVF) or results of intracytoplasmic sperm injection (ICSI) [ 88 ].…”
Section: Targets Of Asas: Assorted Mosaicmentioning
confidence: 99%
“…Studies on ASAs and post-ICSI pregnancy rates have generally shown that ASAs do not affect post-ICSI pregnancy rates [ 59 , 88 , 89 , 90 , 91 ].…”
Section: Targets Of Asas: Assorted Mosaicmentioning
confidence: 99%
“…Thus, serum and follicular fluid share similar IgG and IgA content. Interestingly, among all immunological factors that may affect fertilization and reproductive success, little attention has been paid to antibodies (but see, e.g., antisperm antibodies studies; [ 41 ]), especially to anti-HLA antibodies [ 42 ]. Anti-HLA antibodies are formed in response to contact with non-self HLA antigens after blood transfusion, organ or tissue transplantation, and pregnancy.…”
Section: Introductionmentioning
confidence: 99%